Pemetaan Pandangan dan cita-cita Hidup Warga Muhammadiyah di Eks Karesidenan Surakarta - Joko Subando; Edy Muslimin; Muh Samsuri; Sarilan (Pawarta: Journal of Communication and Da'wah, 2024)
This research aims to produce a mapping of the ideological strength of Muhammadiyah in terms of its perspectives and aspirations within the former Surakarta residency area. The study employs a quantitative approach, focusing on respondents' perceptions regarding Muhammadiyah's views and life aspirations. A total of 208 respondents participated in the study, and data collection utilized a measurement tool for Muhammadiyah's ideological strength developed by Subando, Samsuri, and Muslimin. The collected data were analyzed using descriptive statistics. The research findings indicate that the Muhammadiyah Regional Leaders (Pimpinan Daerah Muhammadiyah, PDM) of Klaten achieved the highest score (4.77), indicating the most favorable assessments of Muhammadiyah's perspectives and aspirations. They were followed by PDM Sukoharjo (4.26), PDM Boyolali (4.25), PDM Surakarta (4.19), and PDM Karanganyar with the lowest score (3.99). Based on these findings, PDM Karanganyar could benchmark against other PDMs and adopt the internalization pattern of strengthening Muhammadiyah's ideology in the Klaten region as a model.